A study on exterior beam to column joint with alternative ductile detailing - Banu, W. Balkis; Jaya, K.P. (Journal of Structural Engineering, 2024)
In seismically vulnerable areas, the beam to column joint is the most critical region in reinforced concrete structures. Because of the long development lengths and large bend diameters, the arrangements for straight bar and hook anchorage in structural concrete create practical problems. Proper anchorage and joint details of reinforcement are essential. The innovative joint designs that can reduce congestion of reinforcement in the joint are desirable. The present study aims to compare the behaviour of exterior beam-column joint with the use of the threaded bar and steel fibers in place of conventional joint detailing. Six joint sub assemblages were tested under reversed cyclic loading. The displacement-controlled reverse cyclic loading was applied at the free end of the beam. A 3D numerical model has been created using the ABAQUS 6.14 software. The Concrete Damage Plasticity (CDP) model was used to define the non-linear features of concrete by analyzing the response of the structure. The performance of an alternative joint detailing, which is practically feasible, is compared with that of a conventional ductile detailing in terms of ultimate load, hysteresis behaviour, crack pattern, energy dissipation, and ductility. The average difference between FEA results and experimental results was less than 5%.